Strategi Bauran Pemasaran dalam Meningkatkan Penjualan Wedding Package di The Anvaya Beach Resort Bali - Ni Komang Wulan Theresia Andari; Luh Putu Citrawati; Ketut Arjaya (Pusat Penelitian Dan Pengabdian Masyarakat STIEPARI Semarang, 2025)
The sales target for wedding packages at The Anvaya Beach Resort Bali in 2020, 2021 and 2023 cannot be achieved. This research aims to identify a marketing mix strategy to increase sales of wedding packages at The Anvaya Beach Resort Bali. This research uses qualitative descriptive data analysis techniques which will be analyzed using SWOT analysis with the 7P marketing mix (Product, Price, Place, Promotion, People, Process and Physical Evidence). SWOT Matrix Analysis groups internal and external factors to produce four specific strategies, namely SO, ST, WO, and WT. In the research results, there are four marketing mix strategies in increasing sales of wedding packages at The Anvaya Beach Resort Bali, namely the SO (Strength Opportunities) strategy of having a wedding venue location which is a strategy to facilitate access in holding weddings, the ST (Strength Threats) strategy of utilizing the wedding venue by promoting The beauty of each wedding location that is owned, the WO (Weakness Opportunities) strategy improves weaknesses by utilizing the potential of social media which provides information about wedding packages to companies, and the WT (Weakness Threats) strategy maximizes ecommerce to expand the reach of the target market.